(Auto)Mobilities and social identities in Portugal - Sales Oliveira, C. (2014)
Mobility is an expression of modernity, and is considered by some an analytical paradigm of contemporary western society (Sheller and Urry, 2006). Stratification, on the other hand, is a classic sociological dilemma. In this article we propose to look at mobility patterns from the point of view of the social composition of their actors in the Portuguese context. Based on the results of PhD research on Portuguese metropolitan mobility patterns, we explore the relationship between mobility and social classes, with particular emphasis on the choice of automobility. We identify different mobility profiles, mainly according to the means of transport and the socio-professional identity of the studied population.